Empowering MSME's through Digital Transformation in Accounting - Hadiono, Kristophorus; Supriyanto, Aji; Adhi, Antono; Singh, Narinderjit Singh Sawaran; Damaryanti, Rr. Fitri (Jurnal Pengabdian Masyarakat Bestari, 2024)
Despite the numerous benefits offered by digitalization, many MSMEs in Malaysia still rely on manual accounting methods. This reliance on manual processes results in inefficiencies, errors, and time-consuming tasks. By leveraging digital tools and technologies, MSMEs can streamline their accounting operations, improve accuracy, and make informed business decisions. This study will investigate the specific challenges and opportunities associated with digitalizing accounting processes in MSMEs, including factors such as cost, technological literacy, and data security. Through a comprehensive analysis, this community service program will propose practical recommendations to facilitate the adoption of digital accounting solutions and empower MSMEs to thrive in the digital age.